2022
DOI: 10.3389/fpubh.2022.876606
|View full text |Cite
|
Sign up to set email alerts
|

Belt and Road Environmental Implications for South Asia

Abstract: The Belt and Road Initiative (BRI) can play a significant role in the sustainable development of South Asia if appropriately implemented. Apart from the economic, trade, and cultural benefits of this colossal infrastructure, less is known about its environmental impact on South Asia. This study looks closely at the potential impact of the BRI on the South Asian environment. This research is based on the government-issued environmental policies, peer-reviewed literature, media articles, and reports. It has been… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 33 publications
0
2
0
Order By: Relevance
“…The McKinsey Global Institute argues that transparency and accountability in government can be enhanced by the digitalization of governments, which in return improves the quality of government services ( Manyika et al, 2013 ). That is why our previous study clubbed CG and digitalization of Beijing’s motivation as striving toward transparency ( Ali et al, 2022 ). Through empirical analysis, Worthy (2015) found that the availability of government data promotes oversight and decreases the probability of corruption.…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…The McKinsey Global Institute argues that transparency and accountability in government can be enhanced by the digitalization of governments, which in return improves the quality of government services ( Manyika et al, 2013 ). That is why our previous study clubbed CG and digitalization of Beijing’s motivation as striving toward transparency ( Ali et al, 2022 ). Through empirical analysis, Worthy (2015) found that the availability of government data promotes oversight and decreases the probability of corruption.…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…The significance of the initiative lies not only in its infrastructure projects, such as the construction of transportation and energy facilities but also in its participation in digital cooperation. However, the initiative has also raised concerns about digital dependency, which is becoming a key issue worthy of in-depth discussion (Ali, M., 2022;. Chinese companies, such as Huawei's assistance in building Kenya's 4G network and participating in the upgrade of the M-PESA mobile payment system, have undoubtedly promoted the digitalization process in these countries.…”
Section: B Bri and Sdg 9: Promoting Resilient Infrastructure And Sust...mentioning
confidence: 99%
“…For example, the World Bank reports that such large-scale transportation projects expose countries and local communities to suffer from carbon dioxide (CO 2 ) emission growth by some 7% in total. 14 In response to the environmental risks and concerns: the BRI has developed multiple sub-routes, such as Digital Silk Road, Clean Silk Road and Green Silk Road to deliver developmental finance to the bilateral or multilateral partnerships with developing countries for green development. 15…”
Section: China’s Shift To Greener Brimentioning
confidence: 99%